Guide to the Uruguay Round agreements - Croome, John (Kluwer Law International The HagueNL, 1999)
Provides an explanation of each agreement, with cross-references to the provisions of the legal text and any associated decisions, including important interpretative decisions that may have been taken since April 1994. Supplies the WTO Secretariat's own analysis of the significance and likely impact of the commitments in the goods and services schedules.